2009
DOI: 10.3899/jrheum.090569
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Metaanalysis of Patient Self-Report versus Trained Assessor Joint Counts in Rheumatoid Arthritis

Abstract: Objective Patient self-report outcomes and physician-performed joint counts are important measures of disease activity and treatment response. This metaanalysis examines the degree of concordance in joint counts between trained assessors and patients with rheumatoid arthritis (RA). Methods Studies eligible for inclusion met the following criteria: English language; compared patient with trained assessor joint counts; peer-reviewed; and RA diagnosis determined by board-certified or board-eligible specialist o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 27 publications
2
42
0
3
Order By: Relevance
“…This may also be a problem in other variables. According to Barton et al (20), joint count performed by a trained assessor, as in the TIRA cohort, and self-reported swollen joints, as in the UCSF cohort, show a low level of correlation. Furthermore, in the TIRA cohort, the slightly modified Swedish version of the HAQ was used.…”
Section: Discussionmentioning
confidence: 99%
“…This may also be a problem in other variables. According to Barton et al (20), joint count performed by a trained assessor, as in the TIRA cohort, and self-reported swollen joints, as in the UCSF cohort, show a low level of correlation. Furthermore, in the TIRA cohort, the slightly modified Swedish version of the HAQ was used.…”
Section: Discussionmentioning
confidence: 99%
“…The included RAPID3 and the RADAI have high reliability [16]. The RADAI is a valid instrument [17,18], and patient reported tender joint count has a moderate to marked correlation to assessment by health professionals [19]. …”
Section: Methodsmentioning
confidence: 99%
“…A systematic review and metaanalysis of patient-reported joint counts found self-reported tender joint counts to have moderate to marked correlation with those performed by a trained assessor 27 . In contrast, swollen joint counts demonstrated lower levels of correlation.…”
Section: Journal Of Rheumatologymentioning
confidence: 99%